Hasmonean realities behind Ezra, Nehemiah, and Chronicles - Finḳelshṭayn, Yiśraʾel 1949- (SBL Press, 2018)
"The book deals with key topics in Ezra, Nehemiah, and 1 and 2 Chronicles, such as the list of returnees, the construction of the city wall of Jerusalem, the adversaries of Nehemiah, the tribal genealogies, and the territorial expansion of Judah in 2 Chronicles. Finkelstein argues that the geographical and historical realities cached behind at least parts of these books fit the Hasmonean period in the late second century BCE. Seven previously published essays are supplemented by maps, updates to the archaeological material, and recent articles on the topics"--
"Archaeological and historical perspectives." - Cover
Keywords: Bible / Chronicles / Criticism, interpretation, etc; Bible / Ezra / Criticism, interpretation, etc; Bible / Nehemiah / Criticism, interpretation, etc; Bible / Chronicles; Bible / Ezra; Bible / Nehemiah; Jews / History / 586 B.C.-70 A.D.; Maccabees; Jews; 586 B.C.-70 A.D.; Criticism, interpretation, etc; History